К воспоминаниям С.Б.Дубровинского (1885-1975) о микробиологах и эпидемиологах: академике АН СССР и президенте Всеукраинской академии наук Д.К.Заболотном, члене-корреспонденте АН СССР С.И.Златогорове, академиках АМН СССР М.А.Морозове и Л.В.Громашевском - Васильев, К.К. (Сумський історико-архівний журнал, 2010)
The article, told before the recollection chapter of an epidemiologist, Doctor of Medicine
professor Samuil Borisovich Dubrovinsky “Recollections about other scientists of domestic
microbiology and epidemiology: D.K.Zabolotny, M.A.Morozov, S.I.Zlatogorov and
L.V.Gromashevsky”, gives explanations and additions to the author’s memoirs.